Mould growth prediction in tropical climate buildings by using hygrothermal differentials - Oladokun, Majeed Olaide (Kulliyyah of Architecture and Environmental Design, Internatioal Islamic University Malaysia, 2015)
The rising energy costs, an aftermath of the energy crises of the 1970s, resulted in stringent measures in buildings' design, construction, operation and maintenance. Amongst the several factors of achieving building energy efficiency, airtightness reduces air-conditioning cooling and heating loads. Nevertheless, building airtightness is found to result in problems amongst which are indoor moisture and resultant mould infestation. As the economic development of Malaysia continues, increased numbers of airtight, fully air conditioned buildings are evolving. The high levels of thermal and hygric conditions throughout the year in this environment underscore the role of mechanical ventilation systems in controlling the indoor hygrothermal conditions. The current standard for energy efficiency in Malaysia makes adequate provision for the thermal performance of buildings but gives little considerations for its moisture performance in relation to energy efficiency. Besides, limited guidelines exist for indoor air quality (IAQ) and mould proliferation in Malaysia and the knowledge among the public is lacking. Therefore, a holistic approach is needed for not only the hygrothermal performance but also the associated mould assessment and prediction in these edifices as early detection of the menace is often difficult until growth has advanced. The study combined in-situ, analytical and numerical experiments. The numerical experiments developed computational fluid dynamics (CFD) simulation models and routines for mould growth prediction from the interaction between the building envelopes and hygrothermal differentials of the indoor and outdoor microclimate in mechanically ventilated building. The developed analytical method executed hygrothermal performance assessment of envelopes between air conditioned and non-air conditioned spaces for condensation risk assessment. The results revealed Penicillium sp., Cladosporium sp., Chaetomium sp., Rhodotorula sp., Fonsecaea sp., Aspergillus sp. and few other species. The numerical simulation was able to predict the hygrothermal profiles triggering the mould growth. The findings also revealed that the operative cooling set-point of 17.3 °C (temperature) and 71.5% (relative humidity) increases condensation risks on the warm side of the envelopes separating air conditioned and non-air conditioned spaces. The risk is reduced by maintaining the operative cooling set-points in the air-conditioned room at 22 °C to 23 °C. This study provides a holistic approach to designing and retrofitting energy efficient buildings that will be free of microbial infestation due to elevated hygrothermal profiles and increased condensation risk. Equally, this study provides awareness of the effect of differential operations in space air-conditioning on indoor moisture as well as adoptable procedures for mould assessment and predictions in the hot and humid climate of Malaysia. Above all, the study will assist in policy formulation that incorporate hygrothermal performance with energy efficiency.